Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: =>5-x=-23
=>x=5+23=28
b: =>x-3-x+7-25+x=54
=>x-21=54
=>x=75
c: =>7-9x-2x+4=-5x-35+27-25=-5x-37
=>-11x+3=-5x-37
=>-6x=-40
=>x=20/3
a.
10-x-5 = (-5) - 7 -11
=>5-x = 0
=>x=5
b
(x-3) - (x+17-24) - (25-x) = 24 - (-30)
=>x - 3 - x - 17 + 24 - 25 - x = 24 + 30
=>-x - 21 = 54
=>-x = 75
=>x = -75
c
(7 - 9x) - (2x - 4) = - (5x + 35) - (-27) - 25
=>7-9x - 2x + 4 = -5x - 35 + 27 - 35
=>11 - 11x + 5x = -43
=>16x = 11 + 43
=>16x = 54
=>x=4
\(Ư\left(30\right)=\left\{1;2;3;5;6;10;15;30\right\}\\ \Rightarrow x=5\left(B\right)\\ B\left(8\right)=\left\{0;8;16;24;32;...\right\}\\ \Rightarrow x=24\left(B\right)\)
5 x 6 = 30 2 x 6 = 12 3 x 6 = 18 4 x 6 = 24
6 x 5 = 30 6 x 2 = 12 6 x 3 = 18 6 x 4 = 24
a. 4(2x+7)-3(3x-2)=24
=> 8x+28-9x+6=24
=> -x+34=24
=> -x=-10=> x=10
b. 2(x-1)+3(x-2)=x-4
=> 2x-2+3x-6=x-4
=> 5x-8=x-4
=> 5x-x=-4+8
=> 4x=4=> x=1
c. [124-(20-4x)]:30+7=11
=> (124-20+4x):30=4
=> (104+4x):30=4
=> 104+4x=120
=> 4x=96 => x=24
a)\(x-\frac{1}{4}=\frac{5}{8}\)
\(x=\frac{5}{8}+\frac{1}{4}\)
\(x=\frac{7}{8}\)
b)\(\frac{x}{12}=\frac{-1}{24}-\frac{1}{8}\)
\(\frac{x}{12}=\frac{-1}{24}+\frac{-1}{8}\)
\(\frac{x}{12}=\frac{-1}{6}\)
\(x=\frac{-1}{6}\times12\)
\(x=-2\)
a)x-1/4=5/8
=>x=5/8+1/4
x=7/8
b) x/12=-1/24-1/8
=>x/12=-1/6
=>x=-2
c).......... Tự làm
a)
\(x-5=-1\)
\(x=-1+5\)
\(x=4\)
b)
\(x+30=4\)
\(x=4-30\)
\(x=-26\)
c)
\(x-(-24)=3\)
\(x+24=3\)
\(x=3-24\)
\(x=-21\)
d)
\(22-(-x)=12\)
\(22+x=12\)
\(x=12-22\)
\(x=-10\)
e)
\(( x + 5 ) + ( x - 9 ) = x + 2\)
\(x+5+x-9=x+2\)
\(x+x-x=2+9-5\)
\(x=6\)
f)
\(( 27 - x ) + ( 15 + x ) = x - 24\)
\(27-x+15+x=x-24\)
\(-x+x-x=-24-15-27\)
\(-x=-66\)
\(x=66\)
x - 5 = -1 x - (-24) = 3
x = -1 + 5 x + 24 = 3
x = 4 x = 3 - 24
x + 30 = 4 x = - 21
x = 4 - 30 22 - ( -x) = 12
x = - 26 22 + x = 12
x + 5 + ( x - 9) = x + 2 x = 12 - 22
x + 5 + x - 9 = x + 2 x = -10
2x - x = 2 - 5 + 9 ( 27 - x) + ( 15 + x) = x - 24
x = - 3 + 9 27 - x + 15 + x = x - 24
x = 6 27 + 15 = x - 24
x - 24 = 42
x = 42 + 24
x = 66
a) 6 x 5 = 30 30 : 6 = 5 30 : 5 = 6
b) 6 x 3 = 18 18 : 6 = 3 18 : 3 = 6
c) 6 x 4 = 24 24 : 6 = 4 24 : 4 = 6
(27-X)+(15+x)=x-24
27-x+15+x=x-24
-x+x-x=-24-27-15
-x=-66
x=-(-66)
x=66
a) x – 5 = - 1 ;
=> x = -1 + 5 = 4
Vậy x = 4
b) x + 30 = - 4;
=> x = - 4 - 30 = - 34
Vậy x = - 34
c) x – ( - 24) = 3 ;
=> x + 24 = 3
=> x = 3 - 24
=> x = - 21
Vậy x = - 21
d) 22 – ( - x ) = 12;
=> 24 + x = 12
=> x = 12
Vậy x = 12
e) ( x + 5 ) + ( x – 9 ) = x + 2 ;
=> x + 5 +x - 9 = x + 2
=> 2x - x = 1 + 9 - 5
=> x = 5
Vậy x = 5
f) ( 27 – x ) + ( 15 + x ) = x – 24 .
=> 27 - x + 15 + x = x - 24
=> x + 42 = x - 24
=> x - x = 42 - 24
=> 0 = 8 ( vô lí)
Vậy x thuộc rỗng
Rảnh nhỉ
@@ Học tốt
## Chiyuki Fujito
3.(24-4:x)=87-30
3.(24-4:x)= 57
(24-4:x)= 57:3
24-4:x= 19
4:x= 24-19
4:x=5
x=5x4
x=20
x= \(\frac{5}{4}\)